Cancer vaccines in colon and rectal cancer over the last decade: lessons learned and future directions. (4th March 2017) - Berry, John; Vreeland, Timothy; Trappey, Alfred; Hale, Diane; Peace, Kaitlin; Tyler, Joshua; Walker, Avery; Brown, Ramon; Herbert, Garth; Yi, Fia; Jackson, Doreen; Clifton, Guy; et al.
ABSTRACT: Introduction : Great advances have been made in screening for and treatment of colorectal cancer (CRC), but recurrence rates remain high and additional therapies are needed. There is great excitement around the field of immunotherapy and many attempts have been made to bring immunotherapy to CRC through a cancer vaccine. Areas c overed : This is a detailed review of the last decade's significant CRC vaccine trials. Expert c ommentary : Monotherapy with a CRC vaccine is likely best suited for adjuvant therapy in disease free patients. Vaccine therapy elicits crucial tumor infiltrating lymphocytes, which are lacking in microsatellite-stable tumors, and therefore may be better suited for these patients. The combination of CRC vaccines with checkpoint inhibitors may unlock the potential of immunotherapy for a much broader range of patients. Future studies should focus on vaccine monotherapy in correctly selected patients and combination therapy in more advanced disease.